Enhanced Thermoelectric Metrics in Ultra-long Electrodeposited PEDOT Nanowires - Taggart, David K; Yang, Yongan; Kung, Sheng-Chin; McIntire, Theresa M; Penner, Reginald M (Nano letters, 2011)
The Seebeck coefficient, S, and the electrical conductivity, σ, of electrodeposited poly(3,4-ethylenedioxythiophene) (PEDOT) nanowires and thin films are reported. PEDOT nanowires were prepared by electropolymerizing 3,4-ethylenedioxythiophene (EDOT) in aqueous LiClO4 within a template prepared using the lithographically patterned nanowire electrodeposition (LPNE) process. These nanowires were 40−90 nm in thickness, 150−580 nm in width, and 200 μm in length. σ and S were measured from 190 K to 310 K by fabricating heaters and thermocouples on top of arrays of 750 PEDOT nanowires. Such PEDOT nanowire arrays consistently produced S values that were higher than those for PEDOT films: up to −122 μV/K (310 K) for nanowires and up to −57 μV/K (310 K) for films. The sample-to-sample variation in S for 14 samples of PEDOT nanowires and films, across a wide range of critical dimensions, is fully explained by variations in the carrier concentrations in accordance with the Mott equation. In spite of their higher |S| values, PEDOT nanowires also had higher σ than films, on average, because electron mobilities were greater in nanowires by a factor of 3.